Soft-computing: An Objective Approach in Varied Diabetes Recognition - Chukwuyeni, Obi Jonathan; Imianvan, A A (British Journal of Healthcare and Medical Research, 2014)
Diabetes is a chronic disorder caused by elevated glucose within the blood stream. The predominant indicator of diabetes include a glucose level of more 125mg/dl in addition to frequent thirst, unusual thirst, extreme fatigue blurred vision and frequent infection. Existing approach for the recognition of diabetes are to two classes (Type I and Type II) in addition to their subjective approach. This research paper proposed an objective approach utilizing soft-computing techniques for the recognition of five class of diabetes.